From Script to Screen : Investigating Translation Strategies in the Differences Found in the Subtitles and Dub of the Movie 'Notre Damen kellonsoittaja' - Laine, Veera (My University, 2024)
In my BA thesis, I investigated translation strategies in audiovisual translation, focusing on subtitling and dubbing, and their impact on the final translation product. The emphasis was placed on the utilisation of translation strategies and their observable manifestations, if evident, in the final products. Additionally, I explored why certain strategies might have been chosen. The research used the Disney movie Notre Damen kellonsoittaja (1996) and original English version The Hunchback of Notre Dame (1996) as the material to base the analysis. A comparative method was employed in this thesis and Jan Pedersen’s translation strategies were used as a tool to categorise the findings. Translation strategies seem to play a significant role in the differences between subtitles and dubs along with other constricting aspects for example space limitations with subtitles or lip movements with dubbing. Additionally, when speculating possible reasons for found differences, it was evident that the role of the translator and the knowledge of the acted process is crucial to understanding the differences further. However, access to these aspects was limited and the analysis was based on the background materials and concluding speculation. Incorporating quantitative methods would offer a more comprehensive understanding of the translation process. Additionally, conducting focused investigations into translator effects and expanding the sample size and diversity of materials would enhance the generalizability of findings. By expanding on these measures, further insight into the relations between translation strategies and the end product of translation can be acquired.
Keywords: audiovisual translation, translation strategies, subtitling, dubbing